REALIZATION OF STATE RESETTLEMENT POLICY IN THE NORTH CAUCASIAN REGION AT THE INITIAL STAGE OF COLLECTIVIZATION: RESETTLEMENT OF GIPSY, KOREANS AND ASSYRIANS - V. R. Istyagin (Гуманитарные и юридические исследования)
The article presents the detailed analysis of historiographic development condition as regards various aspects of resettlement policy in the 20-30th of the XX century in the North Caucasus. An attempt is made to track the main stages and regularities in studying agrarian policy of the USSR, characterizing the main works, and also highlighting the main points of view on this subject.